2016
DOI: 10.1111/ssqu.12244
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Educational and Occupational Expectations Influences on Young Adult Educational Attainment, Income, and Underemployment*

Abstract: Objective. Educational and occupational ambitions are on the rise for adolescents in the United States and there is a national push for more postsecondary education. However, most young adults do not hold bachelor's degrees and many jobs do not require them. The objectives of this study were to focus on the need for aligned expectations and the longitudinal effect on educational attainment, personal income, and underemployment. Methods. The methods used the National Education Longitudinal Study of 1988 (NELS:8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
22
0
3
Order By: Relevance
“…Still, scholars have also found consistently high educational attainment of second‐generation Asian‐Americans (Byun & Park, ; Hsin and Xie ; Lee & Zhou, ; Liu & Yu, ; Ochoa, ) and have tried to understand what contributes to these patterns. Specifically, researchers showed that second‐generation Chinese, Koreans, Japanese, and South Indians report the highest rates of advanced degree expectations, as early as eighth grade (Kao, ), which is an important early predictor of later educational attainment (Feliciano, ; Karlson, ; Schmitt‐Wilson & Faas, ; Sewell, Haller, & Portes, ). Later research also showed high levels of attainment and years of schooling completed by Chinese, Koreans, Japanese, and South Indians (Foner, ; Haller et al, ).…”
Section: The New Second‐generation and Educational Attainmentmentioning
confidence: 99%
“…Still, scholars have also found consistently high educational attainment of second‐generation Asian‐Americans (Byun & Park, ; Hsin and Xie ; Lee & Zhou, ; Liu & Yu, ; Ochoa, ) and have tried to understand what contributes to these patterns. Specifically, researchers showed that second‐generation Chinese, Koreans, Japanese, and South Indians report the highest rates of advanced degree expectations, as early as eighth grade (Kao, ), which is an important early predictor of later educational attainment (Feliciano, ; Karlson, ; Schmitt‐Wilson & Faas, ; Sewell, Haller, & Portes, ). Later research also showed high levels of attainment and years of schooling completed by Chinese, Koreans, Japanese, and South Indians (Foner, ; Haller et al, ).…”
Section: The New Second‐generation and Educational Attainmentmentioning
confidence: 99%
“…Another line of research has examined more closely the connections between student educational expectations and their level of education (Chang, Min, Shi, Kenny, & Loyalka, 2016;Englund, Luckner, Whaley, & Egeland, 2004;Trusty, 2002;Trusty, Plata, & Salazar, 2003). Students' educational expectations are shown to increase as they progress in their education (Entwisle, Alexander, & Olson, 2005;Goyette, 2008;Lowman & Elliott, 2010;Schmitt-Wilson & Faas, 2016). Thus, students in higher stages of education have been found to report they expect to earn a higher degree (Jacob & Wilder, 2010;McDaniel, 2009;Reynolds & Burge, 2008;Turley, Santos, & Ceja, 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Educational aspirations and expectations are measures commonly used in the literature to capture educational goals and ambitions (Schmitt-Wilson & Faas, 2016). Although the direction of much research in education has highlighted associations between both educational aspirations and educational expectations (Beal & Crockett, 2010;Boxer et al, 2011), the two concepts have historically been treated as if they were inseparable.…”
Section: Introductionmentioning
confidence: 99%
“…Such patterns can be extracted from the data to describe prevalent group differences in the cotrajectories of constructs (e.g., Archambault et al, 2010). Alternatively, they are constructed by classifying combinations of individual scores of agency components in terms of how well they fit together (e.g., Denissen et al, 2007;Sabates et al, 2011;Schmitt-Wilson & Faas, 2016). Based on such classifications researchers are in the position of analyzing the trajectory of fit/misfit across time.…”
Section: Translating Concepts Of Co-development Into Statistical Modementioning
confidence: 99%
“…An example is the specification of cotrajectory group membership as outcome of individual and social background factors (Archambault et al, 2010). Another one refers to a score of alignment specified as predictor of socioeconomic outcomes (Sabates et al, 2011;Schmitt-Wilson & Faas, 2016). Finally, multigroup analyses are used to examine potential diversity of patterns of interrelations between variables in a population (see e.g., Verboom, Sijtsema, Verhulst, Penninx, & Ormel, 2014).…”
Section: Translating Concepts Of Co-development Into Statistical Modementioning
confidence: 99%